Effect of a Multispecies Probiotic Mixture on the Growth and Incidence of Diarrhea, Immune Function, and Fecal Microbiota of Pre-weaning Dairy Calves - Wu, Yanyan; Wang, Lili; Luo, Ruiqing; Chen, Hongli; Nie, Cunxi; Niu, Junli; Chen, Cheng; Xu, Yongping; Li, Xiaoyu; Zhang, Wenjun (Frontiers in Microbiology, 2021)
The effects of different doses of a multispecies probiotic (MSP) mixture on growth performance, the incidence of diarrhea rate and immune function and fecal microbial diversity and structure were evaluated in pre-weaning Holstein dairy calves atWK2, WK4, WK6 and WK8. Forty Chinese Holstein female newborn calves were randomly assigned to four treatments with 10 calves in each group, C (control group), T1 (0.5 g MSP/calf/day, T2 (1 g MSP/calf/day) and T3 (2 g MSP/calf/day) groups. The experimental period was 56 days. Growth performance, incidence of diarrhea and total serum concentrations (IgA, IgG and IgM) were analyzed. Bacterial 16S rDNA and fungal ITS genes were high-throughput sequenced for fecal microbiota. The relationships among the populations of the principal fecal microbiota at WK2 and the growth performance or serum immunoglobulin concentrations were analyzed using Pearson’s rank correlation coefficients. The MSP supplementation reduced the incidence of diarrhea in the first four weeks of life, and serum IgA, IgG and IgM concentrations increased between WK2 and WK8 in T3 group. There was an increase in growth performance and reduction in the incidence of diarrhea until WK4 after birth in T3 group, compared with the control, T1 and T2 group. The results of fecal microbiota analysis showed that Firmicutes and Bacteroides were the predominant phyla, with Blautia, Ruminococcaceae_UCG-005, norank_f__Muribaculaceae, Bacteroides, Subdoligranulum and Bifidobacterium being the dominant genera in calf feces. Aspergillus, Thermomyces and Saccharomyces were the predominant fungal phyla. Compared to the control group, the MSP supplementation reduced the relative abundance of Bacteroidetes and increased the relative abundance of Bifidobacterium, Lactobacillus, Collinsella and Saccharomyces at WK2. Thus, the fecal microbial composition was not affected by the MSP mixture, There was a noticeable improvement in growth performance, reduction in calf diarrhea, balance in the intestinal microbiota, and an overall improvement of serum immunity in T3 group, comparing with control, T1 and T2 group during the calves’ early life.. We, therefore, recommend adding 2 g / d of multispecies probiotic mixture supplementation in diets of dairy calves during their first four weeks of life before weaning.